Targeting p110gamma in gastrointestinal cancers: attack on multiple fronts - Falasca, Marco; Maffucci, Tania (Frontiers in Physiology, 2014)
Phosphoinositide 3-kinases (PI3Ks) regulate several cellular functions that are critical for cancer progression and development, including cell survival, proliferation and migration. Three classes of PI3Ks exist with the class I PI3K encompassing four isoforms of the catalytic subunit known as p110α, p110β, p110γ and p110δ. Although for many years attention has been mainly focused on p110α recent evidence supports the conclusion that p110β, p110γ and p110δ can also have a role in cancer. Amongst these, accumulating evidence now supports the conclusion that p110γ is involved in several cellular processes associated with cancer development and progression and indeed this specific isoform has emerged as a novel important player in cancer progression. Studies from our laboratory have identified a specific overexpression of p110γ in human pancreatic ductal adenocarcinoma (PDAC) and in hepatocellular carcinoma (HCC) tissues compared to their normal counterparts. Our data have further established that selective inhibition of this PI3K isoform is able to block PDAC and HCC cell proliferation, strongly suggesting that pharmacological inhibition of this enzyme can directly affect these tumors growth. Furthermore increasing evidence suggests that p110γ plays also a key role in the interactions between cancer cells and tumor microenvironment and in particular in tumor-associated immune response. It has also been reported that p110γ can regulate invasion of myeloid cells into tumors and tumor angiogenesis. Finally p110γ has also been directly involved in regulation of cancer cell migration. Taken together these data indicate that p110γ plays multiple roles in regulation of several processes that are critical for tumor progression and metastasis. This review will discuss the role of p110γ in gastrointestinal tumor development and progression and how targeting this enzyme might represent a way to target very aggressive tumors such as pancreatic and liver cancer on multiple fronts.